The effect of NASM-based corrective exercises on lumbar lordosis angle and selected muscle activity in women with lower cross syndrome: A randomized clinical trial - Somayyeh Ghaffari; Seyed Mohammad Hosseini; Mehdi Gheitasi (PLoS ONE, 2026)
Background Lower Cross Syndrome (LCS) is a complex musculoskeletal condition characterized by muscle weakness and tightness patterns, typically resulting from prolonged and repetitive activities or inactivity. Objective This study examined the effects of eight weeks of NASM corrective exercises on improving the lumbar lordosis angle and muscle activity in women with LCS. Method This randomized controlled trial employed a pre- and post-test design. Thirty women with LCS were randomly assigned to an exercise group (n = 15) or a control group (n = 15). The exercise group underwent the NASM exercise protocol. The lumbar lordosis angle was measured using a 30 cm flexible ruler (KEARING brand, China), and muscle activity (gluteus maximus, hamstrings, erector spinae) was assessed via Myon 320 surface electromyography system (Switzerland) during maximum voluntary isometric contraction. The exercise group completed 24 sessions of the NASM protocol over eight weeks. Data were analyzed using paired t-tests and ANCOVA. Results The results showed that eight weeks of NASM corrective exercises led to a significant between-group difference in the lumbar lordosis angle (F = 24.82, p = 0.001) and the electrical activity of the gluteus maximus muscle (F = 5.11, p = 0.032). Within the exercise group, significant improvements were also observed in the electrical activity of the hamstrings, the maximum voluntary isometric contraction (MVIC) of the gluteus maximus and erector spinae, and the onset timing of the erector spinae activity (p ≤ 0.05). However, in the between-group comparison, no significant difference was observed in the electrical activity of the hamstrings and erector spinae muscles, the maximum voluntary isometric contraction (MVIC), and the start time of muscle activity (p > 0.05 for most comparisons). Conclusion The NASM corrective exercise program was effective in reducing lumbar lordosis and enhancing gluteus maximus activity in women with LCS. These findings support the use of this protocol as a specific intervention for improving these parameters in the studied population. Trial registration IRCT20240805062660N1, Iranian Registry of Clinical Trials (IRCT), (March 1 to May 31, 2024).